Analysis of territorial fragilities through GIScience: A method tested in the Life+ A_GreeNet project to implement urban green infrastructures - Caprari, Giorgio; Malavolta, Simone (TeMA - Journal of Land Use, Mobility and Environment, 2024)
The paper presents the results of an applied research on the Adriatic linear city (Marche, Abruzzo) for the construction of an urban-territorial cognitive framework renewed by GIScience methods/techniques (data processing, remote sensing and scientific indexes). In particular, the contribution presents the method steps for the production of a Risk Map and a geodatabase developed in a GIS (Geographic Information Systems) environment starting from open data to support the analytical phase of the A_GreeNet Life+ project and its aims. In this sense, the intermediate/final outputs of the research lay the foundations for new ways and different perspectives to investigate the urban landscape with a focus on the quality/quantity of green infrastructure, thermal stress and social dynamics. In conclusion, the paper is part of the process of renewing the cognitive processes of urban planning, with special regard to the study of territorial fragilities and urban transformations capable of photographing different territorial geographies and evaluating their resilience to the dynamics of climate change. On this basis, the project will imagine new forestation scenarios and the qualification of the landscape-vegetation system and open spaces for healthier and more liveable cities, in accordance with the planning framework in place.